Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Pada Usaha Trift Kiacabo Perumnas Kota Sorong Provinsi Papua Barat Daya - Brien, Selfita; Suripatty, Roberthair (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to determine the influence of product quality on consumer satisfaction in the kia cabo trift business located on Jln. Basuki Rahmat KM 10.5 Perumnas Sorong City, Southwest Papua Province. In this study, a quantitative approach was used, with a sample of 80 respondents. The sampling technique in this study uses a sampling technique. Data collection in the study used Simple Regression Analysis. Data that has met the requirements for analysis are processed using the help of the SPSS program. From the results of statistical testing, it was found that product quality affects consumer satisfaction of the kia cabo trift business on Jln. Basuki Rahmat KM 10.5 Perumnas Sorong City, Southwest Papua Province. The results of the study can be concluded that the product quality variable has a significant effect on the consumer satisfaction variable.